Study of the incidence and factors affecting postpartum anestrus in Murrah buffaloes around Jammu region - Kalsotra, Rajat; Sharma, Utsav; Kumar, Sharad; Kumar, Sudhir (Buffalo Bulletin, 2016)
The individual history of 250 postpartum Murrah buffaloes were recorded and analyzed to determine the incidence of postpartum anestrus and effect of season of calving, parity and age on occurrence of postpartum anestrus. The incidence of postpartum anestrus was 34.4% and nonsignificantly (P>0.05) higher in summer calved buffaloes, 9 year and above age and in 1st, 6th and above parity buffaloes.